Anti-CD19 CAR T-cell therapy remission despite prior anti-CD19 antibody Tafasitamab in relapsed/refractory DLBCL. (2021) - Tabbara, Nadeem; Gaut, Daria; Oliai, Caspian; Lewis, Tara; de Vos, Sven
Highlights: Disease progression following anti-CD19 monoclonal antibody Tafasitamab treatment should not preclude subsequent anti-CD19 CART-cell therapy. Previous studies have demonstrated sequential anti-CD19 to be effective. Larger studies among R/R DLBCL patients across anti-CD19 modalities are needed to guide sequencing of therapies following initial anti-CD19 therapy. Abstract: Tafasitamab (MOR208) is an Fc-enhanced, humanized, monoclonal antibody that targets CD19. The L -MIND (NCT02399085) trial, an open-label, single-arm, phase II study of Tafasitamab (TAFA) plus lenalidomide (LEN), reported progression-free survival of 16 months in R/R DLBCL patients ineligible for autologous stem cell transplantation. Despite recent advances in anti-CD19 therapy, no clinical evidence exists to direct the sequencing of CAR T cell therapy following relapse after prior anti-CD19 therapy. We present the first published case of TAFA/LEN treatment followed by CAR T therapy with sustained remission. Disease progression following treatment with Tafasitamab may not preclude patients from CAR T cell therapy.